Implementation Report: Embedding Responsible Innovation and Scaling in the CGIAR - Altshul, Helen J. (CGIAR System Organization, 2025)
This report translates conceptual guidance into practice by outlining three levels of adoption, minimal, moderate, and deep engagement/mainstreaming, and identifying the capacity support and facilitation needed to make uptake feasible. It emphasizes light-touch, flexible pathways that encourage peer learning, experimentation, and incremental institutional change within the CGIAR.